ANALISIS KELAYAKAN USAHA TOKO BINTANG CCTV DENGAN METODE BUSINESS MODEL CANVAS DAN ANALISIS SENSITIVITAS - Anggunlhera Alinro Mardlatilla (Journal of Optimization System and Ergonomy Implementation, 2023)
Bintang CCTV store is a retail business that specializes in digital security, namely CCTV cameras. Bintang CCTV store is a result of the development of Bintang Komputer store, which is also located in Jagakarsa. After one year of operation, sales have not been stable, so a feasibility analysis is needed to assess the financial, non-financial, sensitivity, and Business Model Canvas aspects. The results of the financial aspect calculations were applied to three sensitivity conditions: optimistic, best, and pessimistic. Under optimistic conditions, the business is considered feasible with a NPV of Rp236,483,715, a PP of 2 year and 7 months, a PI of 1.51, an IRR of 78,8%, and a BEP of Rp173,641,626. Under best conditions, the business is also considered feasible with a NPV of Rp71,108,423, a PP of 4 years and 4 months, a PI of 1.23, an IRR of 23,8%, and a BEP of Rp173,641,626. However, under pessimistic conditions, the business is considered not feasible with a NPV of -Rp116,747,029, a PP is longer than the target, a PI of 0.93, an IRR of -15,9%, and a BEP of -Rp116,747,029. The non-financial aspects include management and organization, market and marketing, and technical and operational aspects. The Business Model Canvas classifies nine business elements based on the results of interviews.